2018
DOI: 10.2147/ccid.s143085
|View full text |Cite
|
Sign up to set email alerts
|

Genitogluteal porokeratosis: a clinical review

Abstract: Porokeratosis is an uncommon disorder of keratinization that presents with keratotic papules or annular plaques that expand centrifugally with a thread-like elevated border. A distinctive histologic structure, the cornoid lamella, is diagnostic of this disorder and consists of a column of parakeratosis with the absence of the granular layer and dyskeratotic cells in the upper spinous zone. Porokeratosis confined to the genitogluteal region is rare and may be subclassified into three types, namely, classical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 56 publications
(33 reference statements)
0
49
0
Order By: Relevance
“…5 Stone et al, described a similar case, in which a 32-year-old man with a 13-year history of pruritic lesions also confined to the natal cleft and he named it as "perianal inflammatory verrucous porokeratosis. 2 The term genitogluteal porokeratosis refers to the porokeratosis restricted to male and female genitalia and those restricted to buttocks. It can be broadly divided into three groups namely classical porokeratosis restricted to the genital region, ptychotropic porokeratosis and penoscrotal porokeratosis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Stone et al, described a similar case, in which a 32-year-old man with a 13-year history of pruritic lesions also confined to the natal cleft and he named it as "perianal inflammatory verrucous porokeratosis. 2 The term genitogluteal porokeratosis refers to the porokeratosis restricted to male and female genitalia and those restricted to buttocks. It can be broadly divided into three groups namely classical porokeratosis restricted to the genital region, ptychotropic porokeratosis and penoscrotal porokeratosis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the genital region and adjacent areas like buttocks, perineum, groin and proximal thigh may occur as a part of generalised porokeratosis, but porokeratosis localized to the genitogluteal region is rare. 2…”
mentioning
confidence: 99%
“…Several therapeutic options have been described; surgical treatment is optional, depending on the number and size of the lesions. [1][2][3][4] Other treatment options include cryotherapy, CO 2 laser therapy, oral and topical retinoids, topical vitamin D3 analogues, keratolytic agents, topical 5-fluorouracil, and diclofenac sodium 3% gel, all of which have inconsistent effects. A recent review found that topical imiquimod may be a preferred treatment for PM.…”
Section: Dear Editormentioning
confidence: 99%
“…The risk is higher in larger lesions that have been developing over longer periods of time, among the elderly and immunocompromised patients, and especially in linear porokeratosis and PM types. [2][3][4] For all these reasons, GGP treatment and regular followup are recommended. Several therapeutic options have been described; surgical treatment is optional, depending on the number and size of the lesions.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation